2013
DOI: 10.2116/analsci.29.447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Solvents and Salts on the Isomerization Reaction (β→α) of Keggin-type 12-Molybdophosphate Anion

Abstract: Experimental Reagents and chemicalsAll of the chemicals were of analytical grade, and were used without further purification. Mo(VI) and P(V) stock solutions were prepared from Na2MoO4·2H2O and NaH2PO4·2H2O, The isomerization reaction of the β-form of 12-molybdophosphate ([PMo12O40] 3-: PMo12) into the α-form in aqueous-organic mixed media containing various salts was extensively investigated with cyclic voltammetry. It was found that the concentration and type of organic solvent and salt strongly affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…8) [88,89]. The optical and redox properties of the two isomers differ, in that the b-isomer is reduced at more positive potentials and exhibits more intense IVCT bands [34,55,89].…”
Section: Isomerism Of 12-mpa and Its Reduced Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…8) [88,89]. The optical and redox properties of the two isomers differ, in that the b-isomer is reduced at more positive potentials and exhibits more intense IVCT bands [34,55,89].…”
Section: Isomerism Of 12-mpa and Its Reduced Formsmentioning
confidence: 99%
“…8) [88,89]. The optical and redox properties of the two isomers differ, in that the b-isomer is reduced at more positive potentials and exhibits more intense IVCT bands [34,55,89]. This phenomenon is well-known in silicomolybdate chemistry where the two isomers can be isolated in aqueous solution under distinctly different conditions [90e92], but has been overlooked in analytical methods based on phosphomolybdate.…”
Section: Isomerism Of 12-mpa and Its Reduced Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow reduction of the [(PO4)Mo12O36] 3-anion may be due to isomerization between the α-and β-form of the Keggin structure. 8 It has been found that, instead of AN, a low volatile solvent, propylene carbonate (PC), can be used as the solvent for the reduction process. In PC, [(P2O7)Mo18O54] 4-anion is also reduced to the blue molybdopyrophosphate species, of which the spectrum is similar to that produced in AN.…”
Section: Resultsmentioning
confidence: 99%
“…8 3-anion may be due to isomerization between the α-and β-forms of the Keggin structure. 35 Thus, a 10 mM level ATP would not interfere with the PPi colorimetric assay significantly.…”
Section: ·3 Colorimetric Ppi Determination and Adenylation Enzyme Assaymentioning
confidence: 99%